Control of machines (presses) for sheet metal stamping - Pašić, Muhamed H. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper deals with the control of presses for sheet metal stamping. The analysis will be based on the experimental setup of the ram height. The experiment will be done for five different positions, i.e.metal sheet thicknesses. The previous state of the press was such that for every change of a position, i.e. metal sheet thickness it was necessary to adjust the ram height The new solution shown in this paper, makes the process much easier and more efficient. In order to use another position, it will be enough to select a particular position and the ram will be automatically adjusted to a required height. This will speed up production and reduce scrap that would be otherwise created due to adjustment.  The state diagram for the new solution is shown as well as the control program for the new solution. Introduction The introduction of this paper briefly describes the press that is the subject of this paper. This press  has almost 50 different positions. The basic parameters for the press functioning are: top portion of the ram, stroke, feeding angle, release angle and ram height which is discussed in this paper. Experimental adjustment of the ram height In the experimental analysis, five different positions, namely: '”Novi burnik“, „Pedala“, „Ručica gornja“, „Nosilac stikala“, „Ručica mirujuća“ were used and for each one an optimum ram height was determined Implementation of the diagram of the press control states Based on thus obtained optimal heights, a press state diagram was made, serving subsequently as a basis for the equations of state and transition which resulted in a Step 7-based software oackage program for the press operation control. This solution makes the press operation more efficient and productive, i.e. the production is increased and metal waste reduced.Analysis of the  results In the end, all the results of the experimental analysis are summarized, i.e., for each position which was the subject of the analysis, optimum ram heights are given. Then it is shown that for each given case, a program can be created to simulate the operation of the press with the optimum ram height i.e. to set automatically the optimum height when choosing a certain position, thus optimizing the work process. This was shown in the state diagram i.e. in the program designed on the basis of the state diagram. Conclusion In this paper we demonstrate how to make the press operation more efficientThe experimental analysis was performed at five different positions, and the optimum ram heights were determined. Then the equationsof transition and state were written, based on which a program for controlling and adjusting the ram height  and press operation was designed. The ram height had previously been determined manually which increased scrap and reduced the production efficiency and effectiveness. With the new solution, however, the optimum ram height is automatically adjusted upon the position selection, the production is increased and scrap reduced to a minimum.
Keywords: thickness; sheet metal; Pressing; Metals; Machining; Heights; controllability